INSIDER TRADING DALAM PRESPEKTIF HUKUM PIDANA DI INDONESIA - Siti Laillatul Mubarohkah (Dinamika, 2020)
Insider trading in the view of criminal law in Indonesia.Furthermore, this paper raises the formulation of the problem 1. Why is insider trading classified as a form of capital market crime? 2. How to regulate handling of insider trading crime in the capital market in Indonesia.The research method used by the author is the normative juriducal method by taking a statutory approach (statue approach) and a conceptual approach. Collection of legal material’s through the study of literature, with secondary and tertiary primary legal material’s. Furthermore, legal material’s are reviewed and analyzed with the approach used in research to answer the problem formulations in this study. The results of this study, insider trading as one of the crimes in the field of capital market’s can be committed by individual’s and also corporations. The provision’s of criminal sanction’s in insider trading crime itself are regulated in article 104 of the Capital Market Law.Keywords: Insider Trading, Criminal Law, Criminal, Criminal liability. ABSTRAKInsider trading dalam pandangan Hukum Pidana di Indonesia.Selanjutnya karya tulis ini mengangkat rumusan masalah 1.Mengapa insider trading digolongkan suatu bentuk kejahatan tindak pidana Pasar Modal? 2.Bagaimana pengaturan pada Pasar Modal serta penanganan tindak pidana insider trading dalam Pasar Modal di Indonesia? .Metode Penelitian yang digunakan penulis adalah metode yuridis normatif dengan menggunakan pendekatan Undang-Undang (statue approach) dan pendekatan Konseptual (conceptual approach). Pengumpulan bahan hukum melalui studi literatur, dengan bahan hukum primer, sekunder maupun tersier. Selanjutnya bahan hukum dikaji dan dianalisis dengan pendekatan-pendekatan yang digunakan dalam penelitian untuk menjawab rumusan masalah dalam penelitian ini. Hasil penelitian ini, insider trading sebagai salah satu kejahatan di  bidang Pasar Modal dapat dilakukan oleh perseorangan dan juga korporasi. Ketentuan dari sanksi pidana dalam kejahatan insider trading itu sendiri telah diatur dalam Pasal 104 UUPM. Kata Kunci : Insider Trading, Hukum Pidana, Sanksi Pidana.